ACTR-50. EFFECT OF CONCURRENT AND ADJUVANT TEMOZOLOMIDE ON SURVIVAL IN PATIENTS WITH NEWLY DIAGNOSED GRADE III GLIOMAS WITHOUT 1p/19q CO-DELETION: A RANDOMIZED, OPEN-LABEL, PHASE 2 STUDY (INTERIM RESULTS FROM THE KNOG-1101 STUDY). (5th November 2018) - Kim, Chae-Yong; Hwang, Kihwan; Min Kim, Tae; Park, Chul-Kee; Hee Chang, Jong; Jung, Tae-Young; Lee, Dong-Eun; Joo, Jungnam; Choe, Ghee Young; Kim, Yu Jung; Se Choi, Byung; Kim, Jeong Hoon
Abstract: OBJECTIVE: We investigated the efficacy between radiotherapy alone versus concurrent chemoradiotherapy with temozolomide followed by adjuvant temozolomide in Korean adult patients with newly diagnosed non-co-deleted grade III gliomas. METHODS: This was a randomized, open-label, phase 2 study, and the first multicenter, prospective clinical trial for Korean patients with glioma. Eligible patients were aged 18 years or older and had newly diagnosed grade III gliomas with ECOG performance status of 0–2. No co-deletion of chromosome 1p/19q and further genetic biomarker was identified for available subjects. Patients were enrolled at 11 centers, and randomized 1:1 to receive radiotherapy alone (daily fractions of 2 Gy given 5 days per week for 6 weeks, for a total of 60 Gy) [Control group (n=44)], or to receive radiotherapy with daily temozolomide (75 mg/m2/day, 7 days/week from the first to the last day of radiotherapy) followed by six cycles of adjuvant temozolomide (150 to 200 mg/m2/day for 5 days during each 28-day cycle) [Treatment group (n=40)]. The primary endpoint was 2-year progression-free survival (PFS). RESULTS: At the time of the preliminary analysis, PFS at 2 years was 42.2% with treatment group and 37.2% with control group. On univariable analysis, extent of tumor resection, age, and IDH-1 mutant were significantly associated with PFS. On multivariable analysis, IDH-1 mutant was the only significant prognostic factor for PFS (HR0.27; 95% CI, 0.12–0.59; p=0.001). IDH-1 mutant was also the only independent prognostic factors for overall survival (HR0.10; 95% CI, 0.02–0.41; p=0.002). Adverse events over grade 3 were seen in 16 (40.0%) patients with Treatment group, but were mild and reversible. CONCLUSIONS: Radiotherapy with concurrent and adjuvant temozolomide in patients with newly diagnosed non-co-deleted anaplastic gliomas in Korean adults trended toward improved 2-year PFS. The survival benefit of this regimen would need further analysis for long-term follow-up.